Endogenous glucocorticoids may serve as biomarkers for migraine chronification - Yohannes W. Woldeamanuel; Bharati M. Sanjanwala; Robert P. Cowan (SAGE Publishing, 2020)
Aims: The aims of this study were to: (a) identify differences in serum and cerebrospinal fluid (CSF) glucocorticoids among episodic migraine (EM) and chronic migraine (CM) patients compared with controls; (b) determine longitudinal changes in serum glucocorticoids in CM patients; and (c) determine migraine-related clinical features contributing to glucocorticoid levels. Methods: Serum and CSF levels of cortisol and corticosterone were measured using liquid chromatography-mass spectrometry among adult patients with EM, CM, and controls. Serum and CSF samples were collected from 26 and four participants in each group, respectively. Serum glucocorticoids were measured at a second timepoint after 2 years among 10 of the CM patients, six of whom reverted to EM while four persisted as CM. Receiver operating characteristic (ROC) analysis was made to assess the migraine diagnostic performance of glucocorticoids. Regression analysis was conducted to determine the link between glucocorticoid levels and migraine-related clinical variables. Results: CM patients exhibited significantly elevated serum and CSF levels of cortisol and corticosterone compared with controls and EM patients (age, sex, body mass index adjusted; Kruskal-Wallis p  < 0.05). ROC showed area-under-curve of 0.89 to differentiate CM from EM. CM patients with remission had their serum glucocorticoids return to control or near EM levels ( p  < 0.05). Persistent CM showed unremitting serum glucocorticoids. Migraine frequency and disability contributed to increased cortisol, while pain self-efficacy predicted lower cortisol levels ( p  < 0.005). Conclusion: Endogenous glucocorticoids may be biomarkers for migraine progression and for monitoring treatment response. Improving pain self-efficacy skills may help optimize endogenous glucocorticoid levels, which in turn may prevent migraine attacks.